Network Management--New Strategies in Elderly Services for Thai Government - Rattanapipat, Suppamas; Chanpetch, Suwit (International Journal of Social Sciences and Management, 2017)
This study mirrors the increasing importance of network management and also looks at about the devolution of elderly services or social services in general. This survey research was to develop a structural equation model of network management in elderly services. The sample consisted of 556 elderly service providers in Southern part of Thailand. Data were collected using a questionnaire. Findings show the structural equation model had a good fit with the empirical data (χ2 = 767.53, df = 279, RMSEA=0.064, CFI=0.98, SRMR=0.058). The model confirms that 6 factors: trust, mutuality, governance, administration, autonomy and, antecedents possessed effects on network performance. Trust had the highest positive direct effects on network performance, followed by mutuality, governance, and administration respectively, autonomy had negative direct effects and, antecedents only had indirect effect. Therefore, when governments have to work together with partners in elderly services, the problems become more complex so administrators should be concern about these constructs to provide service provisions so that a functional capacity can be maintained for elderly well-being. Int. J. Soc. Sc. Manage. Vol. 4, Issue-4: 232-239